Carbon Dioxide and Water Electrolysis Using New Alkaline Stable Anion Membranes - Kaczur, Jerry J.; Yang, Hongzhou; Liu, Zengcai; Sajjad, Syed D.; Masel, Richard I. (Frontiers in Chemistry, 2018)
The recent development and market introduction of a new type of alkaline stable imidazole-based anion exchange membrane and related ionomers by Dioxide Materials is enabling the advancement of new and improved electrochemical processes which can operate at commercially viable operating voltages, current efficiencies, and current densities. These processes include the electrochemical conversion of CO2 to formic acid (HCOOH), CO2 to carbon monoxide (CO), and alkaline water electrolysis, generating hydrogen at high current densities at low voltages without the need for any precious metal electrocatalysts. The first process is the direct electrochemical generation of pure formic acid in a three-compartment cell configuration using the alkaline stable anion exchange membrane and a cation exchange membrane. The cell operates at a current density of 140 mA/cm2 at a cell voltage of 3.5 V. The power consumption for production of formic acid (FA) is about 4.3 - 4.7 kWh/kg of FA. The second process is the electrochemical conversion of CO2 to CO, a key focus product in the generation of renewable fuels and chemicals. The CO2 cell consists of a two-compartment design utilizing the alkaline stable anion exchange membrane to separate the anode and cathode compartments. A nanoparticle IrO2 catalyst on a GDE structure is used as the anode and a GDE utilizing a nanoparticle Ag/imidazolium-based ionomer catalyst combination is used as a cathode. The CO2 cell has been operated at current densities of 200 to 600 mA/cm2 at voltages of 3.0 to 3.2 respectively with CO2 to CO conversion selectivities of 95 - 99%. The third process is an alkaline water electrolysis cell process, where the alkaline stable anion exchange membrane allows stable cell operation in 1 M KOH electrolyte solutions at current densities of 1 A/cm2 at about 1.90 V. The cell has demonstrated operation for thousands of hours, showing a voltage increase in time of only 5 µV/h. The alkaline electrolysis technology does not require any precious metal catalysts as compared to polymer electrolyte membrane (PEM) design water electrolyzers. In this paper, we discuss the detailed technical aspects of these three technologies utilizing this unique anion exchange membrane.